2017
DOI: 10.1016/j.biortech.2017.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Energy consumption and water-soluble protein release by cell wall disruption of Nannochloropsis gaditana

Abstract: Several cell disruption methods were tested on Nannochloropsis gaditana, to evaluate their efficiency in terms of cell disintegration, energy input and release of soluble proteins. High-pressure homogenization (HPH) and bead milling were the most efficient with >95% cell disintegration, ±50% (w/w) release of total proteins and low energy input (<0.5kWh.kg). Enzymatic treatment required low energy input (<0.34kWh.kg), but it only released ±35% protein (w/w). Pulsed Electric Field (PEF) was neither energy-effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 43 publications
6
55
2
Order By: Relevance
“…Furthermore, low-cost applications of microalgae require the use of fresh biomass to avoid the previous costly drying even though microorganisms preserve their cell wall intact, which hinder the bioproducts recovering. Disruption techniques such as bead milling and high-pressure homogenization have demonstrated to be very effective and relatively energy-efficient methods [12,13] though they require specific equipment for which inversion costs are only feasible for some applications [8][9][10]. In contrast, from an operational point of view, alkaline and/or enzymatic methods could be characterized by their simplicity and therefore applicable to low-cost uses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low-cost applications of microalgae require the use of fresh biomass to avoid the previous costly drying even though microorganisms preserve their cell wall intact, which hinder the bioproducts recovering. Disruption techniques such as bead milling and high-pressure homogenization have demonstrated to be very effective and relatively energy-efficient methods [12,13] though they require specific equipment for which inversion costs are only feasible for some applications [8][9][10]. In contrast, from an operational point of view, alkaline and/or enzymatic methods could be characterized by their simplicity and therefore applicable to low-cost uses.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we measured a protein yield of 22.5 % and an E m of 0.607 ± 0.002 kWh kg DW -1 . Safi et al, (2017a) reported yields from 23 to 51 % and corresponding energy consumptions of 0.1 to 0.6 kWh kg DW -1 for the microalgae Nannochloropsis gaditana using bead milling and high pressure homogenization. Such high yields reflect structural differences between the two algae strains, since both works implemented comparable operation conditions for the case of the bead milling (BM) process.…”
Section: Protein Yields and Energy Consumptionmentioning
confidence: 99%
“…2C, all the protein bands expected for T. suecica (Postma et al, 2016) are preserved, confirming the mildness of the present extraction process. (Postma et al, 2016;Postma et al, 2015;Safi et al, 2017a)), EF: Electric Fields ('t Grimi et al, 2014;Parniakov et al, 2015;Postma et al, 2016;Safi et al, 2017a), US: Sonication (Grimi et al, 2014;Parniakov et al, 2015;Passos et al, 2015;Safi et al, 2014c;Wenjuan et al, 2013), HPH: High Pressure Homogenization (Grimi et al, 2014;Safi et al, 2017aSafi et al, , 2014aSafi et al, , 2014c, MW: Microwaves (Passos et al, 2015), Thermal processing (Jazrawi et al, 2015;Passos et al, 2015), Em min : Minimum specific energy for cell rupture (Günther et al, 2016;Lee et al, 2013), Em Ext : Target maximum specific energy for extraction (Coons et al, 2014;Illman et al, 2000).…”
Section: Protein Yields and Energy Consumptionmentioning
confidence: 99%
See 2 more Smart Citations